Dampak Poligami terhadap Psikologis Anak - Fajarwati (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2021)
Polygamy is something very sensitive and most painful for women (wives) andchildren. Although Islam allows polygamy, it is difficult for them (wife and children)to accept. Why is that, because love and time will be divided. This paper examinesthe psychological impact of polygamy on children. There are several negative effectsof polygamy on children's psychological. Among them the child feels less loved, thebirth of hatred in the child against a father, the loss of self-confidence in the childand the child will experience trauma. Parents must realize that the growth anddevelopment of children is very important. Parents are responsible for their children.Parents must prioritize children's interests compared to their own interests. Allahwill hold us accountable for every action we (parents) do. If you are unable to actfairly, then don't polygamy